Identification and Analysis of BCAS4/hsa-miR-185-5p/SHISA7 Competing Endogenous RNA Axis in Late-Onset Alzheimer’s Disease Using Bioinformatic and Experimental Approaches - Sabaie, Hani; Talebi, Mahnaz; Gharesouarn, Jalal; Asadi, Mohammad Reza; Jalaiei, Abbas; Arsang-Jang, Shahram; Hussen, Bashdar Mahmud; Taheri, Mohammad; Jalili Khoshnoud, Reza; Rezazadeh, Maryam (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is a heterogeneous degenerative brain disorder with a rising prevalence worldwide. SHISA7 (CKAMP59) has emerged as one of the most intriguing new members of the SHISA family, in that, unlike other CKAMP counterparts, it exhibits a direct function in inhibitory synaptic GABAAR regulation. The Gene Expression Omnibus database included two microarray datasets, including information on mRNAs (GSE106241) and miRNAs (GSE157239) from individuals with AD with different degrees of AD-associated neurofibrillary pathology in the temporal cortex (TC) tissue specimens and corresponding controls were downloaded from the Gene Expression Omnibus database. The limma package in the R software was used to identify differently expressed mRNAs (DEmRNAs) and miRNAs (DEmiRNAs) associated with AD-related neurofibrillary pathology. Additionally, we used the quantitative polymerase chain reaction technique to examine the expression of the BCAS4/hsa-miR-185-5p/SHISA7 ceRNA axis in the peripheral blood (PB) of fifty AD patients and fifty control subjects. BCAS4 was shown to act as a ceRNA to control the SHISA7 expression throughout AD-associated neurofibrillary pathology in TC tissue specimens by sponging hsa-miR-185-5p, based on our bioinformatics study. Furthermore, in PB specimens from individuals suffering from AD and normal controls, we found no substantial differences in BCAS4 expression patterns. SHISA7 expression in AD patients’ PB was found to be reduced, as was the case in the TC. On the other hands, we discovered reduced amounts of hsa-miR-185-5p in AD patients’ PB samples compared to control subjects, unlike in TC tissue, where it had been demonstrated to be overexpressed. BCAS4 and SHISA7 expression levels showed a strong positive correlation, suggesting the presence of an interconnected network, most likely as a result of ceRNA regulation among PB specimens. The present study is the first evidence to highlight the expression of the BCAS4/miR-185-5p/SHISA7 ceRNA axis in the brain and PB of AD patients. This study improves the existing understanding of the GABAergic system linked with GABAAR and offers a new viewpoint on molecular processes underlying AD pathogenic mechanisms despite the need for more research into the possible roles of this ceRNA axis.